Radial Nerve Fascicular Transfer Preserving Long Head through Anterior Incision for Transhumeral Targeted Muscle Reinnervation - Mustafa Chopan, MD; David Spencer Nichols, BS; Harvey Chim, MD, FACS (Plastic and Reconstructive Surgery, Global Open, 2022)
Summary:. New developments in targeted muscle reinnervation promise better options for treatment of neuropathic pain and improved prosthetic control. For transhumeral amputations, the traditional approach involves an anterior incision to access the median and ulnar nerves and a second posterior incision to access the radial nerve. This is necessitated as exposure of motor branches of the radial nerve distal to the branch to the long head of the triceps is difficult from the anterior approach. Herein, we describe a technique for transferring the radial nerve proper distal to the long head branch to a motor branch to the medial or lateral head of the triceps through internal neurolysis and fascicular transfer. This allows all surgical steps to be performed through a single incision while preserving native motor branches to the biceps and triceps muscles.